Beehives - Kalz, Jill (North Mankato, MN Smart Apple Media, 2002)
Simple text and photographs explain beehive architecture, types of honeybees,and how bees communicate. Also includes a hands-on: Getting the Message Right.
Keywords: Beehives; Honeybee; Bees